Strumenti musicali e fonti letterarie (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2010)
This paper presents a collection of literary sources concerning  trumpets in the Greek and Latin perspective, with the aim to delimit the functions and the meanings of these instruments in the Etruscan World. The study of the ancient texts investigates many aspects related to this group of instruments, with the assumption that they are filtered by the Greek and Latin languages and perception. Some features, such as its multi-functional value, shape, technique, and sonorous quality have been related to some interesting and stimulating issues of  ethnomusicological research. This approach did not have the purpose to discover connections and answers to the problems posed by the doubtful statements of literary sources, but to open the discussion also to the symbolical aspects of the instrument and from this  to recover its profound human significance. The research is then focused on the functions of the trumpets attested in the Etruscan world, and on the lituus, which represents the most interesting instrument of music of these people. The analysis of literary sources allows the writer to suppose that the thyrrenikè salpinx does not automatically designate the lituus, and that therefore the latter  must not necessarily be the war instrument the Etruscans are remembered to have used during battles. It can indeed have been used as insignia of religious and political power, as also its particular sonority suggests. This argument is consistent both with the interpretation given by M. Bonghi Jovino for the lituus of Tarquinia and with the literary suggestions of a ceremonial and sacred function of the ancient trumpets.